2010
DOI: 10.1038/leu.2009.283
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic plasticity of hTERT gene promoter determines retinoid capacity to repress telomerase in maturation-resistant acute promyelocytic leukemia cells

Abstract: The expression of hTERT gene, encoding the catalytic subunit of telomerase, is a feature of most cancer cells. Changes in the chromatin environment of its promoter and binding of transcriptional factors have been reported in differentiating cells when its transcription is repressed. However, it is not clear whether these changes are directly involved in this repression or only linked to differentiation. In a maturation-resistant acute promyelocytic leukemia (APL) cell line (NB4-LR1), we have previously identif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
41
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(43 citation statements)
references
References 46 publications
2
41
0
Order By: Relevance
“…One of these mechanisms could be mediated by WT1, a transcriptional repressor of hTERT. In TG20 cells, we showed that the WT1 binding site, which is present in the distal region of the tert promoter, was unmethylated, a condition required for WT1 repression of htert transcription 32,33…”
Section: Discussionmentioning
confidence: 98%
“…One of these mechanisms could be mediated by WT1, a transcriptional repressor of hTERT. In TG20 cells, we showed that the WT1 binding site, which is present in the distal region of the tert promoter, was unmethylated, a condition required for WT1 repression of htert transcription 32,33…”
Section: Discussionmentioning
confidence: 98%
“…In contrast, transformation of TERT -expressing stem cells such as hematopoetic stem cells may not require promoter mutation to maintain TERT expression through tumorigenesis. As an alternative to mutation, TERT promoter activation may occur through an epigenetic switch(53). Stern et al 2015 has additionally suggested that TERT promoter mutations can convert the silent TERT promoter into an active chromatin state(54).…”
mentioning
confidence: 99%
“…In the same line, aberrant hTERT promoter hypermethylation correlates with elevated hTERT gene expression in the majority of non-infant Sonic-Hedgehog subgroup medulloblastoma tumors [46] whereas hTERT promoter methylation was shown to correlate with reduced hTERT gene expression in B-cell lymphocytic leukemia and childhood acute lymphoblastic leukemia (ALL) [47,48]. Alterations in the epigenetic pattern of hTERT promoter, e.g., by point mutations, may also lead to a deregulation of promoter activity [49,50]. In this line, recurrent genomic rearrangements in the chromosomal region at 5p15.33 proximal of the hTERT gene induced massive chromatin remodeling and DNA methylation leading to the transcriptional upregulation of hTERT expression and telomerase activity in high-risk neuroblastomas [51].…”
Section: Regulatory Mechanisms Involved In Tert Gene Regulation Inmentioning
confidence: 99%